Tailored virtual reality and mobile application for motor rehabilitation - Lourenço F.; Postolache, O.; Postolache, G. (2018 IEEE International Instrumentation and Measurement Technology Conference, I2MTC 2018, 2018)
The present work presents a measurement system and methodology for hand and finger motor rehabilitation. The interaction with serious games developed in Unity 3D game engine is performed using a natural user interface based on Leap Motion Controller. The storage and management of data related to patient identification, established training plans and training results in LeaPhysio system, is realized in a client server architecture. The stored information can be accessed through a developed LeaPhysio App for Android OS platform, which also allows configuration of training plan by a therapist. Different metrics were included in the measurement system to provide to users the possibility to evaluate in an objective way the motor rehabilitation. The tests have shown that the developed system can provide accurate data on hand and finger movements in a meaningful and motivating exercise environment.